Taxonomic review of Tipula (Vestiplex Bezzi) crane flies (Diptera: Tipulidae) in Mongolia - Starkevich, Pavel; Podenas, Sigitas; Gelhaus, Jon K. (Zootaxa, 2020)
Fourteen species of Tipula (Vestiplex Bezzi, 1924) crane flies (Diptera, Tipulidae) known from Mongolia are taxonomically revised. Identification keys for males and females, redescriptions and illustrations of all species are presented. Most genital structures are illustrated for the first time. Tipula (V.) jakut Alexander, 1934 is designated as junior synonym of T. (V.) sintenisi Lackschewitz, 1933; T. (V.) kamchatkana Alexander, 1934 is designated as junior synonym of T. (V.) mediovittata Mik, 1889. Tipula (V.) balioptera Loew, 1863 and T. (V.) leucoprocta Mik, 1889 are listed as new records for the Mongolian fauna.